HUBUNGAN SENI DAN SEJARAH MENURUT MELVIN RADER DAN BERTRAM JESSUP - Johnny Prasetyo (Dewa Ruci: Jurnal Pengkajian dan Penciptaan Seni, 2008)
History can mean either the past actions of human beings or the narrative of such actions based upon inquiry and interpretation.  Taking history in the second mean- ing, we can say that art and history are akin.  Art has a relatively close relation to history.  That is why, this article will give further attention to the artist as historian, art and cultural history, the historian as artist and, the last but not least, art and history allied but distinguishable. Key words: art, history.